A block hydrogen absorber with high efficiency hydrogen absorption effect and preparation method thereof

By mixing vinyl polysiloxane with powder hydrogen absorbing agent and molding it, a high-density bulk hydrogen absorbing agent is prepared, which solves the problem of difficult application of existing powder hydrogen absorbing agents in complex environments and achieves high efficiency , fast hydrogen absorption effect.

CN115646158BActive Publication Date: 2025-02-07GENERAL ENG RES INST CHINA ACAD OF ENG PHYSICS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202211231285.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-09
Publication Date
2025-02-07
Estimated Expiration
2042-10-09

AI Technical Summary

Technical Problem

Existing powder hydrogen absorbing agents are difficult to meet the hydrogen absorption requirements of complex shapes and sizes in a closed environment, and their low density and packaging problems limit their application range.

Method used

A high-density bulk hydrogen absorbing agent is prepared by mixing vinyl polysiloxane with a powder hydrogen absorbing agent and adding a curing agent for molding. This method not only improves the density and shape flexibility of the hydrogen absorbing agent, but also enhances its hydrogen absorbing properties.

Benefits of technology

The bulk hydrogen absorbing agent exhibits a high saturated hydrogen absorption amount and a fast hydrogen absorption rate. It can effectively absorb hydrogen in complex environments, reduce the risk of hydrogen accumulation, and is suitable for application scenarios in a variety of shapes and sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115646158B_ABST
    Figure CN115646158B_ABST
Patent Text Reader

Abstract

The invention provides a block hydrogen absorber with high-efficiency hydrogen absorption effect and a preparation method thereof, and relates to the technical field of hydrogen absorption material preparation; the block hydrogen absorber comprises vinyl polysiloxane and powder hydrogen absorber, and the mass ratio of vinyl polysiloxane to powder hydrogen absorber is 2-15:98-85; the preparation method of the block hydrogen absorber is as follows: S1 first prepares polysiloxane, and dissolves the prepared polysiloxane in a solvent to obtain a mixed solution; S2 adds the mixed solution to the powder hydrogen absorber, stirs evenly, then adds a curing agent and a catalyst, and stirs continuously; after mixing evenly, evaporates the solvent to obtain powder, and molds, demolds, and solidifies the powder to obtain the block hydrogen absorber; the block hydrogen absorber can be processed into a block with a required shape and size according to use requirements, has a high saturated hydrogen absorption amount and hydrogen absorption rate, and can be widely used in the nuclear industry and electrical component fields as a hydrogen absorption material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen absorbing material preparation, in particular to a block hydrogen absorbing agent with high-efficiency hydrogen absorbing effect and a preparation method thereof. Background Art

[0002] Since hydrogen is flammable and explosive and can quench metals with hydrogen, it is necessary to control the concentration of hydrogen in the field of electrical components and the defense industry to eliminate the adverse effects of hydrogen accumulation. Hydrogen elimination in open spaces usually only requires ventilation to displace and eliminate, but in some closed environments such as sealed electronic components, hydrogen cannot be eliminated by displacement and elimination because the seal of the device cannot be opened. In these closed spaces, materials with hydrogen absorption properties are needed to absorb hydrogen to ensure the function of the device and extend the service life of the device. The most widely used organic hydrogen absorber was first reported by the Los Alamos Laboratory in the United States and is produced by Honeywell. The organic hydrogen absorber is a complex of a polyacetylenic compound (usually p-diphenylethynylbenzene) and a palladium-carbon catalyst. It appears as a black powder with a density of approximately 0.6 g / cm 3 , the particle size is usually less than 50μm, and it will flow with the airflow when the airflow passes through. Although organic hydrogen absorbers have been widely used in fields such as nuclear waste transportation, this type of powder hydrogen absorber also has a series of shortcomings, which limit its application in a wider range of fields. First of all, the density of powder hydrogen absorbers is relatively small. For some compact equipment systems, due to limited internal space, there will be a problem of insufficient total hydrogen absorption when used. Secondly, this type of hydrogen absorber is a powder and must be packaged when used, otherwise there will be a problem of polluting the use environment. The use of packaging bags further increases the volume and mass of the system, which is not conducive to use. Finally, for complex environments such as gaps and curved surfaces, powder hydrogen absorbers and bagged hydrogen absorbers are difficult to meet the installation requirements of these use environments; the development of block hydrogen absorbers with specific sizes and shapes is of great significance to meet the hydrogen absorption needs of various complex environments such as electrical components.

[0003] In the prior art, methods for preparing rubber elastic materials with hydrogen absorption properties have been disclosed, and these methods can be used to prepare elastic hydrogen absorption materials with specific shapes and sizes. Patent CN 105153449 A reports a method for preparing a hydrogen absorption film using polymethylvinylsiloxane as a substrate by a method of hydrosilylation curing. The document (DOI: 10.3390 / ma14081853) expands the system in CN 105153449 A and further conducts a systematic study on the relationship between the preparation method and the hydrogen absorption performance. From the reported hydrogen absorption effect, it can be seen that the saturated hydrogen absorption capacity of the hydrogen absorption film is about 110-190ml / g, but the hydrogen absorption rate of the film hydrogen absorber is slow, and the hydrogen absorption capacity of the hydrogen absorption film with the highest saturated hydrogen absorption capacity in pure hydrogen for 10 minutes is only 85ml / g. The low hydrogen absorption rate of the hydrogen absorption film is closely related to the characteristics of the system. The unsaturated bonds inside the film can only come into contact and react after hydrogen diffuses into the film. Therefore, the reaction rate is restricted by the two steps of hydrogen diffusion and unsaturated bond addition, and therefore significantly decreases. It should be noted that the lower hydrogen absorption rate means that the hydrogen in the use environment of the hydrogen absorption film cannot be removed in time, and there is a possible accumulation of hydrogen concentration. When the accumulation reaches a certain concentration, there is a possibility of combustion and explosion. The ideal hydrogen absorption material should have both high saturated hydrogen absorption capacity and large hydrogen absorption rate, as well as rapid and irreversible hydrogen desorption characteristics. Another disadvantage of the hydrogen absorption film is that the hydrogen absorption effect of the system (hydrogen absorption amount and hydrogen absorption rate) is closely related to the thickness of the film. Our experimental test results show that as the film thickness increases from 200μm to 1000μm, the hydrogen absorption amount and hydrogen absorption rate of the system drop sharply. Therefore, the hydrogen absorption elastomers reported above can only be used in the form of films, and the actual use scenarios are very limited.

[0004] Patent CN 109384976 A uses acetylenic carbon nanomaterials to load noble metal catalysts and compound with unsaturated rubber, and vulcanization obtains a variety of hydrogen-absorbing elastomer materials with hydrogen absorption properties, with a hydrogen absorption capacity of about 130 ml / g. Its design concept and preparation method are similar to those of CN 105153449 A; Patent CN 109384976 A does not give the hydrogen absorption reaction curve of the sample, so it is impossible to know the hydrogen absorption rate data. However, since the matrix used is still a polymer, it can be inferred that its hydrogen absorption rate is low, which can also be confirmed by using a thin film sample when testing the saturated hydrogen absorption capacity in its embodiment. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a block hydrogen absorber with efficient hydrogen absorption effect and a preparation method thereof; the block hydrogen absorber is obtained by mixing a powder hydrogen absorber and vinyl polysiloxane, adding a curing agent, pressing and molding, demolding and further curing; the block hydrogen absorber has an extremely high saturated hydrogen absorption capacity and a very large hydrogen absorption rate.

[0006] The present invention is achieved through the following technical solutions:

[0007] A block hydrogen absorber with high-efficiency hydrogen absorption effect, the block hydrogen absorber comprises vinyl polysiloxane and a powder hydrogen absorber, the mass ratio of the vinyl polysiloxane to the powder hydrogen absorber is 2-15:98-85.

[0008] In the above scheme, vinyl polysiloxane is selected as the adhesive because polysiloxane has strong thermal and radiation aging stability, and long-term use will not cause changes in the appearance of the hydrogen absorbing material and loss of hydrogen absorbing properties due to aging of the material. In addition, polymethylvinylsiloxane contains a large number of double bonds, which can also be catalytically hydrogenated. In addition, rubber materials usually have good elasticity and air permeability, which can ensure that the final material has good mechanical properties and hydrogen absorption properties. The mass ratio of the siloxane to the hydrogen absorbent powder in the material preparation is 2-15:98-75. The vinyl group in vinyl polymethylsiloxane can also undergo reduction and hydrogen absorption under palladium carbon catalysis, so it also contributes to the final hydrogen absorption of the material.

[0009] By using a small amount of vinyl polysiloxane to bond the traditional powder hydrogen absorber, a block hydrogen absorber with a specific desired shape and size can be obtained. The powder in the block hydrogen absorber is piled up under molding to form a continuous structure with micropores, which is conducive to the diffusion of hydrogen. Therefore, the block hydrogen absorber has a high hydrogen absorption capacity and hydrogen absorption rate that hydrogen absorption films do not have. In addition, due to the high density of the block hydrogen absorber (about 1.0g / cm 3 ), so the block hydrogen absorber has a higher hydrogen absorption capacity per unit volume, which has advantages that powder hydrogen absorbers do not have for applications in limited spaces. In addition, the shape and size of the block hydrogen absorber can be designed by changing the size and shape of the mold in the molding step to meet the needs of a variety of usage environments.

[0010] Preferably, the vinyl polysiloxane has the following structure:

[0011]

[0012] The sum of m and n is in the range of 50-8000, and the molar content of the repeating unit vinylmethylsiloxane is in the range of 5%-100%. In this scheme, too low viscosity of the vinyl polysiloxane will reduce the final bonding strength, which will have an adverse effect on the molding of the block hydrogen absorbing material.

[0013] Preferably, the powdered hydrogen absorber comprises a noble metal catalyst and a phenylacetylene compound; in the powdered hydrogen absorber, the content of the noble metal catalyst is 20wt% to 55wt%.

[0014] Preferably, the phenylethynyl alkynyl compound is DEB or DPB; the structure is as follows:

[0015]

[0016] Preferably, the noble metal catalyst is porous carbon, porous alumina, porous ceramic or porous graphite loaded with zero-valent palladium or platinum; wherein the noble metal loading is 5wt% to 20wt%. DEB and DPB have a high saturated hydrogen absorption capacity, which can ensure that the final material has a high saturated hydrogen absorption capacity. Palladium catalyst is the most common catalyst with good catalytic performance in commercial use, which can ensure that the final material has good hydrogen absorption performance (hydrogen absorption amount and hydrogen absorption rate).

[0017] Preferably, the thickness of the block hydrogen absorber is greater than 0.5 mm. Thicker materials have higher crushing force and a wider range of application.

[0018] In addition, to achieve the above object, the present invention also provides a method for preparing the block hydrogen absorber with high efficiency hydrogen absorption effect as described above, comprising the following steps:

[0019] S1: first preparing polysiloxane, and dissolving the prepared polysiloxane in a solvent to obtain a mixed solution;

[0020] S2: adding the mixed solution to the powdered hydrogen absorber, stirring evenly, adding a curing agent and a catalyst, and stirring continuously; after the mixture is evenly mixed, evaporating the solvent to obtain a powder, and molding, demolding, and curing the powder to obtain the block hydrogen absorber.

[0021] In the above scheme, by dissolving the prepared polysiloxane in a solvent, its contact and mixing with the powder hydrogen absorber can be increased, the appearance smoothness and strength of the block hydrogen absorber after molding can be improved, and the mixing of the components can be promoted, thereby improving the performance and quality of the product; after mixing, the curing agent hydrogen silicone oil and the catalyst are added, and after mixing again, they are molded to a predetermined shape and size, and after demolding, the block hydrogen absorber with high efficiency hydrogen absorption effect can be obtained by curing; the above preparation method has simple conditions and easy operation, which is conducive to large-scale production. In addition, in the preparation process of block hydrogen absorption materials, it is necessary to control multiple conditions such as the proportion of each component, processing method and curing method, so as to control the microscopic morphology of the material, and then obtain a composite material with high saturated hydrogen absorption capacity and high-speed hydrogen absorption effect.

[0022] Preferably, the curing agent is polymethyl hydrogen siloxane having the following structure:

[0023] The values ​​of m and n are in the range of 8-2000, and the molar fraction of the repeating unit hydrogen methyl siloxane is 8%-100%. The amount of the curing agent added is 2wt%-10wt% of the mass of the vinyl polysiloxane.

[0024] Preferably, the catalyst is a compound containing zero-valent platinum, such as a card catalyst:

[0025]

[0026] Preferably, in step S2, the temperature of the curing reaction after demoulding is 55-100° C. At this temperature, the curing of the polysiloxane adhesive can be promoted to obtain a bulk hydrogen getter with no defects in appearance.

[0027] When the above-mentioned bulk hydrogen absorber absorbs hydrogen, the following will occur: Fig.18 The chemical reaction shown, wherein the unsaturated organic matter in the material is DEB.

[0028] Specifically, the starting material DEB will undergo stepwise addition (BE) under hydrogen until a saturated product F is generated; in addition, if the polysiloxane contains residual vinyl groups from curing, the following chemical reactions will also occur simultaneously:

[0029]

[0030] wherein m is a positive integer, and m+n is less than 2000; after the reaction, hydrogen is added to the unsaturated bonds, thereby achieving the purpose of eliminating hydrogen in the atmosphere.

[0031] The beneficial effects of the present invention are:

[0032] 1. The method of the present invention can be used to prepare a bulk hydrogen absorber with high-efficiency hydrogen absorption characteristics. This type of material can be processed into a block with a specific shape and size according to the actual environment requirements, overcoming the defects of traditional powder hydrogen absorbers that need to be packaged and used and are difficult to adapt to complex application space environments.

[0033] 2. The block hydrogen absorption material has a high saturated hydrogen absorption capacity and hydrogen absorption rate, overcoming the defects of the reported elastomeric film hydrogen absorption material, which has a low hydrogen absorption rate and cannot meet the requirements of thicker use environments; the hydrogen absorption capacity of this material in a pure hydrogen environment for 1 minute is greater than 100 ml / g, and the hydrogen absorption capacity after 10 minutes is greater than 150 ml / g.

[0034] 3. The preparation method provided by the present invention is simple and efficient, has the characteristics of being scalable, and can meet the needs of actual batch production. The prepared hydrogen absorbing material can be widely used in the nuclear industry and the field of electrical components. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 : In Example 1, the hydrogen absorption curve of the powder hydrogen absorber;

[0036] Figure 2 : In Example 1, when the vinyl content is 100wt%, 1H NMR graph of polymethylvinylsiloxane;

[0037] Figure 3 : In Example 1, when the vinyl content is 50wt%, 1H NMR graph of polymethylvinylsiloxane;

[0038] Figure 4 : In Example 1, when the vinyl content is 25wt%, 1H NMR graph of polymethylvinylsiloxane;

[0039] Figure 5 : The hydrogen absorption reaction curve of the hexagonal hydrogen absorption block prepared in Example 1;

[0040] Figure 6 : The hydrogen absorption reaction curve of the hexagonal hydrogen absorption block prepared in Example 2;

[0041] Figure 7 : The hydrogen absorption reaction curve of the hexagonal hydrogen absorption block prepared in Example 3;

[0042] Figure 8 : In Example 4, the hydrogen absorption curve of the powdered hydrogen absorber;

[0043] Fig. 9 : The hydrogen absorption reaction curve of the hexagonal hydrogen absorption block prepared in Example 4;

[0044] Fig.10 : The hydrogen absorption reaction curve of the hexagonal hydrogen absorption block prepared in Example 5;

[0045] Fig.11 : The hydrogen absorption reaction curve of the hexagonal hydrogen absorption block prepared in Example 6;

[0046] Fig.12 : In Comparative Example 1, the hydrogen absorption curve of the hydrogen absorption film with a thickness of 200 μm;

[0047] Fig.13 : In Comparative Example 1, the hydrogen absorption curve of the hydrogen absorption film with a thickness of 500 μm;

[0048] Fig.14 : In Comparative Example 1, the hydrogen absorption curve of the hydrogen absorption film with a thickness of 1000 μm;

[0049] Fig.15 : In Comparative Example 2, the hydrogen absorption curve of the hexagonal hydrogen absorption material prepared;

[0050] Fig.16 : In Comparative Example 3, the hydrogen absorption curve of the hexagonal hydrogen absorption material prepared;

[0051] Fig.17 : Electron photos of powdered hydrogen absorbers and bulk hydrogen absorbers;

[0052] Fig.18 : Schematic diagram of hydrogen absorption principle. DETAILED DESCRIPTION

[0053] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0054] Example 1

[0055] Preparation of powder or powder hydrogen absorber: weigh 70g of p-diphenylethynylbenzene and 30g of dry 5wt% palladium carbon, add them into a 500ml stainless steel grinding jar, then add 200g of stainless steel grinding beads (100g each of 2mm and 0.2mm diameter steel beads), cover the lid and fix it on the ball mill, grind for 15min, stop for 5min and grind 30 times in a forward and reverse rotation alternating manner; after completion, open the grinding jar, use a 200-mesh stainless steel sample sieve to sieve out the hydrogen absorber, and seal it for standby use.

[0056] The hydrogen absorption reaction curve of the powder hydrogen absorber prepared by this method is as follows Figure 1 shown.

[0057] Preparation of polysiloxane: Take a 500 ml two-necked flask, add a stirrer and 0.3 g of a methanol solution of tetramethylammonium hydroxide (10 wt%), then heat to 100° C. and evacuate for 30 min to remove the methanol, and then add nitrogen.

[0058] Weigh a certain proportion of octamethylcyclotetrasiloxane and 60g of tetramethyltetravinylcyclotetrasiloxane, add them to the catalyst tetramethylammonium hydroxide from which the solvent has been removed under a nitrogen atmosphere, then add 100ml of toluene, stir and react at 100°C, stop heating after reacting for 6 hours, and wait for the obtained viscous liquid to cool and then precipitate into methanol; collect the polymer layer, dissolve it in THF and sink it into methanol again; repeat twice and then rotary evaporate to remove the solvent to obtain a colorless, transparent, viscous liquid.

[0059] Add 50 g of the obtained colorless, transparent, viscous liquid into a 250 ml flask, add a stirrer and pass nitrogen to remove the air in the system, add 50 ml of toluene under a nitrogen atmosphere, and after complete dissolution, add 0.5 ml of triethylamine and 0.5 ml of trimethylsilyl chloride in sequence. Stir and react at room temperature for 18 hours. After the reaction is completed, the obtained liquid is precipitated into methanol. The polymer is collected and dissolved in THF and precipitated repeatedly twice. After rotary evaporation of the solvent, a colorless, transparent, viscous liquid is obtained.

[0060] The vinyl content in the product can be obtained by adjusting the proportion of tetramethyltetravinylcyclotetrasiloxane in the mixed monomer; wherein, the NMR spectra of the polymers prepared by using 100wt%, 50wt% and 25wt% of tetramethyltetravinylsiloxane in the experiment are as follows: Figure 2-4 shown.

[0061] Preparation of rectangular hydrogen absorbing material: weigh 3g polymethylvinylsiloxane (M n ~150kDa, vinyl content 38wt%) was dissolved in 15ml of n-hexane, 30g of powdered hydrogen absorber was added, and after stirring and mixing evenly, 0.12g of polymethylhydrogensiloxane (viscosity 15-40mPa·s) and 15μL of card catalyst were added, and stirring was continued until the mixture was evenly mixed. After that, the solvent was evaporated by rotary evaporation, and the obtained black powder was filled into a mold (the mold cavity size was 2cm*4cm*5mm, and the mass of powder added to each mold cavity was 5.0g), and the tablet was pressed on a tablet press at 30kg / cm 2 After demoulding, the obtained block was placed in a 55°C oven for curing for 20 hours to obtain a defect-free and smooth rectangular hydrogen absorption material; the hydrogen absorption reaction curve of the hydrogen absorption material is shown in Figure 5 shown.

[0062] Example 2

[0063] Weigh 1.5 g polymethylvinylsiloxane (M n ~150kDa, vinyl content 38wt%) was dissolved in 15ml of n-hexane, added to 30g of powdered hydrogen absorber, stirred and mixed evenly, then 0.12g of polymethylhydrogensiloxane (viscosity 15-40mPa·s) and 15μL of card catalyst were added, and stirring was continued until the mixture was evenly mixed. After that, the solvent was evaporated by rotary evaporation, and the obtained black powder was filled into a porous mold (the mold cavity size was a hexagon with a side length of 2cm*5mm, and the filling amount per hole was 4.0g), and the tablet was pressed on a tablet press at 30kg / cm 2 After demoulding, the obtained block was placed in a 55°C oven for curing for 20 hours to obtain a defect-free and smooth hexagonal hydrogen absorbing material; the hydrogen absorption reaction curve of the hydrogen absorbing material is shown in Figure 6 shown.

[0064] Example 3

[0065] Weigh 1.5 g polymethylvinylsiloxane (M n~150kDa, vinyl content 3wt%) was dissolved in 15ml of n-hexane, added to 30g of powdered hydrogen absorber, stirred and mixed evenly, then 0.12g of polymethylhydrogensiloxane and 15μL of card catalyst were added, and stirring was continued until the mixture was evenly mixed. After that, the solvent was evaporated by rotary evaporation, and the obtained black powder was filled into a porous mold (the mold cavity size was a hexagon with a side length of 2cm*5mm, and the filling amount per hole was 4.0g), and the tablet was pressed on a tablet press at 30kg / cm 2 The obtained block was placed in an oven at 55°C for curing for 20 hours to obtain a defect-free and smooth hexagonal hydrogen absorbing material. The hydrogen absorption reaction curve of the hydrogen absorbing material is shown in FIG. Figure 7 shown.

[0066] Example 4

[0067] Preparation of powdered hydrogen absorbent

[0068] Weigh 70g of 1,4-diphenyldibutyne and 30g of dry 5wt% palladium carbon, and add them to a 500ml stainless steel grinding jar. Add 200g of stainless steel grinding beads (100g each of 2mm and 0.2mm diameter steel beads), cover the lid and fix it on the ball mill. Grind for 15 minutes, stop for 5 minutes, and grind 30 times in a forward and reverse rotation. After completion, open the grinding jar, use a 200-mesh stainless steel sample sieve to sieve out the hydrogen absorber, and seal it for standby use; the hydrogen absorption reaction curve of the powdered hydrogen absorber is shown in the figure below. Figure 8 shown.

[0069] Weigh 1.5 g polymethylvinylsiloxane (M n ~150kDa, vinyl content 38wt%) was dissolved in 15ml of n-hexane, added to 30g of hydrogen absorbing powder, stirred and mixed evenly, then 0.12g of polymethylhydrogensiloxane (viscosity 15-40mPa·s) and 15μL of card catalyst were added, and stirring was continued until the mixture was evenly mixed. After that, the solvent was evaporated by rotary evaporation, and the obtained black powder was filled into a porous mold (the mold cavity size was a hexagon with a side length of 2cm*5mm, and the filling amount per hole was 4.0g), and the tablet was pressed on a tablet press at 30kg / cm 2 After demoulding, the obtained block was placed in a 55°C oven for curing for 20 hours to obtain a defect-free and smooth hexagonal hydrogen absorbing material; the hydrogen absorption reaction curve of the hydrogen absorbing material is shown in Fig. 9 shown.

[0070] Example 5

[0071] Weigh 3.0 g of vinyl polysiloxane (M n~131kDa, vinyl content 15wt%) was dissolved in 15ml of n-hexane, added to 30g of hydrogen absorbing powder, stirred and mixed evenly, then 0.12g of polymethylhydrogensiloxane (viscosity 15-40mPa·s) and 15μL of card catalyst were added, and stirring was continued until the mixture was evenly mixed. After that, the solvent was evaporated by rotary evaporation, and the obtained black powder was filled into a porous mold (the mold cavity size was a hexagon with a side length of 2cm*5mm, and the filling amount per hole was 4.0g), and the tablet was pressed on a tablet press at 30kg / cm 2 After demoulding, the obtained block was placed in a 55°C oven for curing for 20 hours to obtain a defect-free and smooth hexagonal hydrogen absorbing material; the hydrogen absorption reaction curve of the hydrogen absorbing material is shown in Fig.10 shown.

[0072] Example 6

[0073] Weigh 3.0 g of polymethylvinylsiloxane (M n ~163kDa, vinyl content 38wt%) was dissolved in 15ml of n-hexane, added to 30g of hydrogen absorbing powder, stirred and mixed evenly, then 0.12g of polymethylhydrogensiloxane (viscosity 200-600mPa·s) and 15μL of card catalyst were added, and stirring was continued until the mixture was evenly mixed. After that, the solvent was evaporated by rotary evaporation, and the obtained black powder was filled into a porous mold (the mold cavity size was a hexagon with a side length of 2cm*5mm, and the filling amount per hole was 4.0g), and the tablet was pressed on a tablet press at 30kg / cm 2 After demoulding, the obtained block was placed in a 55°C oven for curing for 20 hours to obtain a defect-free and smooth hexagonal hydrogen absorbing material; the hydrogen absorption reaction curve of the hydrogen absorbing material is shown in Fig.11 shown.

[0074] Comparative Example 1

[0075] Thin film hydrogen absorbing materials

[0076] Weigh 2.0 g of polymethylvinylsiloxane (M n ~150KDa) in a 100ml PP beaker, add 0.8g 5wt% palladium carbon catalyst and stir evenly, then add 50mg hydrogenated silicone oil and 10μL card catalyst and continue stirring until uniform. Then the mixture is coated on a PTFE film and scraped on a coating machine to a thickness of 250μm, and then cured at 65℃ for 24h to obtain a low-strength black elastic film.

[0077] Repeating the above process and changing the scraping height, a 500μm black film can be obtained. A 1mm thick film is obtained by forming a film again on a 0.5mm film.

[0078] The hydrogen absorption reaction curves of films with different thicknesses (200μm, 500μm, 1000μm) in a pure hydrogen environment are shown below: Figure 12-14 shown.

[0079] Comparative Example 2

[0080] Weigh 15.0 g of vinyl polysiloxane (M n ~163kDa, vinyl content 38wt%), add it to 15g hydrogen absorbing powder, stir and mix evenly, and then pass it through the mill several times to mix evenly. Then add 0.88g polymethylhydrogensiloxane (viscosity 200-600mPa·s) and 15μL card catalyst, and continue to pass it through the mill until it is evenly mixed. The obtained black solid is filled into a porous mold (the mold cavity size is a hexagon with a side length of 2cm*5mm, and the filling amount per hole is 4.0g), and molded on a tablet press at a pressure of 30kg / cm2. After demolding, the obtained block is placed in a 55℃ oven for curing for 20h to obtain a defect-free and smooth hexagonal hydrogen absorbing material; the hydrogen absorption reaction curve of the hydrogen absorbing material is shown as follows Fig.15 shown.

[0081] Comparative Example 3

[0082] Weigh 9g polybutadiene (M n ~220kDa), add 21g hydrogen absorbing powder, stir and mix evenly, then thinly pass through on an open mill for several times to mix evenly, then add 0.15g of double two five, and continue to thinly pass through until mixed evenly. The obtained black solid is filled into a porous mold (the mold cavity size is a hexagon with a side length of 2cm*5mm, and the filling amount per hole is 4.0g), and vulcanized on a flat vulcanizer (140℃, 10MPa). After demolding, a defect-free and smooth hexagonal hydrogen absorbing material is obtained; the hydrogen absorption reaction curve of the hydrogen absorbing material is shown in the figure below Fig.16 shown.

[0083] Since commercial polybutadiene cannot be vulcanized at low temperatures, the activity of the catalyst is affected under high-temperature vulcanization, so the saturated hydrogen absorption capacity of the resulting hydrogen absorption block is significantly reduced.

[0084] Comparative Example 4

[0085] Weigh 0.3 g of vinyl polysiloxane (M n ~163kDa, vinyl content 38wt%) was dissolved in 15ml of n-hexane, added to 30g of hydrogen absorbing powder, stirred and mixed evenly, then 0.02g of polymethylhydrogensiloxane (viscosity 200-600mPa·s) and 15μL of card catalyst were added, and stirring was continued until the mixture was evenly mixed. After that, the solvent was evaporated by rotary evaporation, and the obtained black powder was filled into a porous mold (the mold cavity size was a hexagon with a side length of 2cm*5mm, and the filling amount per hole was 4.0g), and the tablet was pressed on a tablet press at 30kg / cm 2The mold is pressed under pressure and loose powder is obtained after demoulding.

[0086] In addition, in addition to the powder hydrogen absorber, hexagonal hydrogen absorber block and rectangular hydrogen absorber block in the above-mentioned embodiments 1-6, a cylindrical hydrogen absorber block can also be prepared according to actual use requirements, wherein the electronic photos of the powder hydrogen absorber, hexagonal hydrogen absorber block, rectangular hydrogen absorber block and cylindrical hydrogen absorber block are as follows: Fig.17 shown.

[0087] in conclusion:

[0088] It can be seen from Examples 1-6 that the material in the present invention is a block hydrogen absorbing material with both high saturated hydrogen absorption capacity and hydrogen absorption rate; the saturated hydrogen absorption capacity of the material is greater than 180ml / g, and the hydrogen absorption capacity after reacting in pure hydrogen for 1min and 10min is greater than 100ml / g and 150ml / g. It is processed into a specific shape and size according to the use requirements, which can meet the needs of various actual installation environments, overcomes the defects of traditional powder hydrogen absorbers that need to be packaged and are difficult to adapt to complex application scenarios; it also overcomes the defects of the reported thin film hydrogen absorption materials with small hydrogen absorption capacity and hydrogen absorption rate, and is more in line with the use requirements of real scenarios.

[0089] The hydrogen absorption amount and hydrogen absorption rate of the thin film hydrogen absorption material in Comparative Example 1 decrease significantly with the increase of thickness. It can be seen from the figure that the hydrogen absorption amount of the thin film hydrogen absorption material in pure hydrogen for 1 minute and 10 minutes is less than 50ml / g and 80ml / g, respectively. The hydrogen absorption rate is low, and hydrogen accumulation may occur in the use environment during use.

[0090] The mass ratios of the vinyl polysiloxane and the powder hydrogen absorber in Comparative Examples 2 and 4 are both outside the scope to be protected by the present invention; the mass of the vinyl polysiloxane in Comparative Example 2 is too large, and the presence of too much polysiloxane matrix seriously hinders the diffusion of hydrogen in the hydrogen absorbing material, so the saturated hydrogen absorption capacity of the obtained 5 mm high hexagonal hydrogen absorption block is significantly reduced, and even the prepared hexagonal hydrogen absorption block has basically no hydrogen absorption effect; the mass of the vinyl siloxane in Comparative Example 4 is too small, and too little adhesive makes it impossible to obtain a whole block of hydrogen absorption material during molding, and a loose powder is obtained after demolding, which looks similar to hydrogen absorption powder and cannot be used alone without outer packaging.

[0091] In Comparative Example 4, a terminal hydroxyl polybutadiene containing double bonds was used instead of polyvinyl methylsiloxane as a binder to prepare a bulk hydrogen absorber, and the curing agent was bismaleic anhydride. Since the curing agent has a certain poisoning effect on the precious metal catalyst of the system, the obtained sample basically has no hydrogen absorption characteristics, and the saturated hydrogen absorption capacity is less than 30 ml / g.

[0092] In addition, although polyvinyl siloxane is disclosed in the prior art, such as CN201911169286.5 and CN201510673143.3, and powdered hydrogen absorbent is disclosed in CN201910584761.9, a bulk hydrogen absorbent with excellent comprehensive properties cannot be obtained by simply mixing the above polyvinyl methyl siloxane and powdered hydrogen absorbent. The non-optimized raw material ratio (polyvinyl methyl siloxane, hydrogen absorbing powder, solvent and catalyst) and preparation conditions (molding pressure, molding density and curing temperature, etc.) in the preparation will lead to a variety of problems such as a decrease in the saturated hydrogen absorption capacity and hydrogen absorption rate of the final material, powder loss before hydrogen absorption, and cracking after hydrogen absorption.

[0093] The above are only preferred embodiments of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the present invention through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A bulk hydrogen absorbing material with high efficiency hydrogen absorbing effect, characterized in that: The bulk hydrogen absorbing material comprises vinyl polysiloxane and a powder hydrogen absorbing agent, and the mass ratio of the vinyl polysiloxane to the powder hydrogen absorbing agent is 2-15:98-85; The vinyl polysiloxane has the following structure: Wherein, the sum of m and n is in the range of 50-8000, and the molar content of the repeating unit vinylmethylsiloxane is in the range of 5%-100%; The powder hydrogen absorber comprises a noble metal catalyst and a phenylacetylene compound; in the powder hydrogen absorber, the content of the noble metal catalyst is 20 wt% to 55 wt%; The phenylacetylene alkynyl compound is DEB or DPP; 。 2. The block material with high efficiency hydrogen absorption effect according to claim 1, characterized in that: The noble metal catalyst is porous carbon, porous alumina, porous ceramic or porous graphite loaded with 0-valent palladium or platinum; wherein the loading amount of the noble metal is 5 wt% to 20 wt%.

3. The block material with high efficiency hydrogen absorption effect according to claim 1, characterized in that: The thickness of the block hydrogen absorbing material is greater than 0.5 mm.

4. The method for preparing a high-efficiency bulk hydrogen absorbing material according to any one of claims 1 to 3, characterized in that: The steps include: S1: preparing polysiloxane first, and dissolving the prepared polysiloxane in a solvent to obtain a mixed solution; S2: adding the mixed solution to the powdered hydrogen absorber, stirring evenly, adding a curing agent and a catalyst, and stirring continuously; after being evenly mixed, evaporating the solvent to obtain a powder, and molding, demolding, and curing the powder to obtain the block hydrogen absorber.

5. The method for preparing a bulk material with high efficiency hydrogen absorption effect according to claim 4, characterized in that: The curing agent is a polymethyl hydrogen siloxane having the following structure: The values ​​of m and n range from 8 to 2000, and the molar fraction of the repeating unit hydrogen methyl siloxane is 8% to 100%.

6. The method for preparing a bulk hydrogen absorbing material with high efficiency hydrogen absorbing effect according to claim 4, characterized in that: The catalyst is a compound containing zero-valent platinum.

7. The method for preparing a bulk hydrogen absorbing material with high efficiency hydrogen absorbing effect according to claim 4, characterized in that: In the step S2, the temperature of the curing reaction after demoulding is 55-100 ° C.

Citation Information

Patent Citations

  • High-molecular composite thin film capable of absorbing hydrogen and preparation method of high-molecular composite thin film

    CN105153449A

  • A kind of polymer composite film capable of absorbing hydrogen and its preparation method

    CN105153449B

  • Preparation method of flexible hydrogen-eliminating film material

    CN109384976A

  • Irreversible hydrogen absorbing porous composite material preparation method and product thereof

    CN110193361A

  • Preparation method of a novel polysiloxane hydrogen absorption polymer film material

    CN110951262A